Immigration nation: aid, control, and border politics in Morocco - Gazzotti, Lorena (Cambridge University Press, 2024)
"1 Introduction Power works by making it hard to challenge how power works. Sara Ahmed On the morning of 9 September 2016, a large crowd gathered at the convention centre of Hay Ryad, one of the wealthiest neighborhoods of the Moroccan capital Rabat. All those who mattered in the migration world were there: Moroccan high-ranking civil servants, European diplomats, representatives from international, Moroccan and migrant non-governmental organisations (NGOs), and of course, officers of the International Organisation for Migration (IOM) and the United Nations High Commissioner for Refugees (UNHCR)"--